2008
DOI: 10.4067/s0716-078x2008000400006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the marine picocyanobacteria Prochlorococcus and Synechococcus assessed by terminal restriction fragment length polymorphisms of 16S-23S rRNA internal transcribed spacer sequences

Abstract: In order to assess the appropriateness of the use of internal transcribed spacer (ITS) sequences for the study of population genetics of marine cyanobacteria, we amplified and cloned the 16S rRNA gene plus the 16S-23S ITS regions of six strains of Prochlorococcus and Synechococcus. We analyzed them by denaturing gradient gel electrophoresis (DGGE) and terminal restriction fragment length polymorphisms (T-RFLP). When using the standard application of these techniques, we obtained more than one band or terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Tree topologies of cyanobacterial CynS matched phylogenies based on 16S rRNA, ITS and ntcA (12,21,28,30,33), and branching was supported by strong posterior probabilities. Based on these observations, we suggest that cynS was common in ancestral cyanobacteria and cynS was lost from many modern cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Tree topologies of cyanobacterial CynS matched phylogenies based on 16S rRNA, ITS and ntcA (12,21,28,30,33), and branching was supported by strong posterior probabilities. Based on these observations, we suggest that cynS was common in ancestral cyanobacteria and cynS was lost from many modern cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The barcoded primers consisted of adapter A (forward) or B (reverse) + Key (TCAG) + barcode (10 bp oligonucleotide, forward only) + picocyanobacteria-specific primers. The ITS-af (5'-GGA TCA CCT CCT AAC AGG GAG-3') and ITS-ar (5'-GGA CCT CAC CCT TAT CAG GG-3') primers were used as specific primers (Lavin et al 2008). The ITS-af and ITS-ar primers showed perfect matches to 99% of the 2389 picocyanobacterial ITS sequences obtained from cultures and clone libraries, indicating high specificity to picocyanobacteria.…”
Section: Pyrosequencing Of Its Sequencesmentioning
confidence: 99%
“…These studies have revealed the existence of diverse Synechococcus and Prochlorococcus clades or ecotypes. Most studies of picocyanobacterial distribution in marine environments have been conducted using dotblot hybridization and real-time quantitative polymerase chain reaction (qPCR) methods using cladespecific probes (Fuller et al 2003, Zwirglmaier et al 2008, Tai & Palenik 2009, Post et al 2011, Ahlgren & Rocap 2012 or terminal restriction fragment length polymorphism (Lavin et al 2008). Recently, barcoded pyrosequencing methods that identify short taxonomic molecular markers via 454 sequencing technologies have been used to analyze microbial diversity in various environments (Binladen et al 2007, Qian et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oxycline in the study area has the genetic potential to perform various processes, as has been indicated by several studies that show the presence of amo-A genes, coding for the active subunit of the AMO enzyme (Molina et al 2007), and nirS and nosZ genes, coding for NO − 2 and N 2 O reductase, respectively (Castro-González et al 2005; Castro-González, Ulloa, and Farías 2015). In addition, the oxycline base may coincide with the presence of a secondary fluorescence maximum where high relative abundances of Prochlorococcus and Synechococcus have been observed (Lavin et al 2008(Lavin et al , 2010. These cyanobacteria are able to assimilate NO − 2 via nitrite reductase, given that they lack nitrate reductase (Moore, Rocap, and Chisholm 1998;Partensky and Garczarek 2010;Zehr and Kudela 2011).…”
Section: Discussionmentioning
confidence: 88%
“…c. Effects of NO − 2 plus DOC addition on net N 2 Od cycling in the UBOMZ at the offshore station Table 2 presents the results for the experiments carried out under induced anoxic conditions at the base of the oxycline, where nutrients and/or DOC limitation may prevail. At that depth, low NO − 2 levels (0.22 μM) were registered onboard (Lavin et al 2008(Lavin et al , 2010. Furthermore, the addition of NO − 2 and DOC stimulated the denitrifying community and resulted in higher N 2 Opd (up to 78.8 nM d −1 ) and N 2 Ocd (58.71 nM d −1 ) rates than those observed at the UBOMZ at the coastal station.…”
Section: B Effects Of Anoxia On Net N 2 Od Cycling Along the Upper Omentioning
confidence: 78%